2005
DOI: 10.1258/0956462052932629
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic hepatitis C infection on outcomes of patients with an advanced stage of HIV-1 infection in an area of low prevalence of co-infection

Abstract: To ascertain whether hepatitis C (HCV) co-infection affects the progression of HIV infection, we initiated an eight-year prospective observational study at a university hospital in Taiwan where seroprevalences of HCV antibody and HIV antibody were low. Fifty-three (12.0%) consecutive non-haemophiliac HIV-1-infected patients with HCV co-infection and 387 (88.0%) patients without HCV and hepatitis B co-infection were enrolled between June 1994 and June 2002 and observed until December 2002. Outcomes evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
3
15
2
Order By: Relevance
“…In this study, the prevalence of HCV/HIV co-infection was 52.1% (293/562), which is substantially higher than the prevalence reported by Hung et al in Taiwan during the period from 1994 to 2002 (9.6%) [38]. This discrepancy might be due to the difference in study populations: a prison-based population in the current study versus a hospital-based population in Hung's study.…”
Section: Discussioncontrasting
confidence: 77%
“…In this study, the prevalence of HCV/HIV co-infection was 52.1% (293/562), which is substantially higher than the prevalence reported by Hung et al in Taiwan during the period from 1994 to 2002 (9.6%) [38]. This discrepancy might be due to the difference in study populations: a prison-based population in the current study versus a hospital-based population in Hung's study.…”
Section: Discussioncontrasting
confidence: 77%
“…A likely explanation for such an observation is that coincident with the dramatic increase of CRF07_BC-infected cases in 2004 and 2005, the prevalence of HCV in HIV-1-infected IDUs was much higher after 2004 (54% vs. 95%, p ϭ 0.011) because the prevalence of HCV in HIV-1-infected individuals who were not IDUs in our cohort did not increase (7% vs. 10%, p ϭ 0.256). 26 Therefore, this HIV-1 outbreak among IDUs in Taiwan is likely accompanied by HCV coinfection, similar to the HIV-1 outbreak observed among IDUs in China. 14,15 The clustering pattern of our pilot analysis of the HCV genotype using NS5B sequences amplified from HIV/HCV coinfected individuals suggested that HCV transmission could have occurred on at least three separate occasions, giving rise to the circulation of genotypes 1a, 1b, and 6a (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Among the total of 1160 titles/abstracts screened, 52 papers were selected for in-depth review. Seven papers provided data from eras pre- and post- HAART introduction [11, 17-22]. For pre-HAART analysis, 10 studies were excluded for one or more of the following reasons: 1) AIDS and overall mortality were combined as a single endpoint [17, 23, 24], 2) lack of HCV-negative control [21, 25, 26] or 3) data were not able to be pooled [22, 27-29].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported a strong association between HCV/HIV coinfection and increased risk of HIV disease progression [8, 9], while other studies have not confirmed this result after the widespread use of HAART [10, 11]. This systematic review estimates the effect of HCV on both mortality and HIV progression in HCV/HIV coinfected patients in the era of HAART.…”
Section: Introductionmentioning
confidence: 99%